Impact of the Chromatin Remodeling Factor CHD1 on Gut Microbiome Composition of Drosophila melanogaster - Sebald, Johanna; Willi, Michaela; Schoberleitner, Ines; Krogsdam, Anne; Orth-Höller, Dorothea; Trajanoski, Zlatko; Lusser, Alexandra (PloS one, 2016)
The composition of the intestinal microbiota of Drosophila has been studied in some detail in recent years. Environmental, developmental and host-specific genetic factors influence microbiome composition in the fly. Our previous work has indicated that intestinal bacterial load can be affected by chromatin-targeted regulatory mechanisms. Here we studied a potential role of the conserved chromatin assembly and remodeling factor CHD1 in the shaping of the gut microbiome in Drosophila melanogaster. Using high-throughput sequencing of 16S rRNA gene amplicons, we found that Chd1 deletion mutant flies exhibit significantly reduced microbial diversity compared to rescued control strains. Specifically, although Acetobacteraceae dominated the microbiota of both Chd1 wild-type and mutant guts, Chd1 mutants were virtually monoassociated with this bacterial family, whereas in control flies other bacterial taxa constituted ~20% of the microbiome. We further show age-linked differences in microbial load and microbiota composition between Chd1 mutant and control flies. Finally, diet supplementation experiments with Lactobacillus plantarum revealed that, in contrast to wild-type flies, Chd1 mutant flies were unable to maintain higher L. plantarum titres over time. Collectively, these data provide evidence that loss of the chromatin remodeler CHD1 has a major impact on the gut microbiome of Drosophila melanogaster.